Introduction of Hadamard Coded Modulation For Optical fiber communications systems (International Journal of Engineering and Computer Science, 2015)
- Orthogonal Frequency Division Multiplexing (OFDM) is considered to be a promising technique against the multipath fading channel for wireless communications. OFDM is a multiplexing technique that is useful in wireless transmission of data. OFDM system is use for high speed applications. The OFDM-related technique has been invented over 40 years ago, but it has gone through many advancements over the years . OFDM for wireless communications has intensively been an active research area in the past 10 years. Hadamard transform modulation is also one of the latest approach for modifications in the OFDM to bring some advantage to it. Due to its various advantages, the HCM can be used in optical fibre applications,Radio Over fiber is one of it. In this paper, HCM and its use in OFDM has been discussed for the application of Rof.